Synthesis of cyano-polycarbosilane and investigation of its pyrolysis process. Issue 15 (December 2020) - Chen, Dou; Mo, Gaoming; Qian, Junmin; He, Liu; Huang, Qing; Huang, Zhengren
Abstract: Polycarbonsilane (PCS) is an important precursor of silicon carbide (SiC) fibers and ceramics. The ceramic yield of PCS is relatively low, about 60 %, which may bring some deficiencies in its applications. In this work, a novel precursor cyano-polycarbosilane (PCSCN) is synthesized by hydrosilylation reaction between PCS and acrylonitrile using a rhodium-containing catalyst, although acrylonitrile is generally not easy for hydrosilylation. After introducing tiny amounts of cyano (-C≡N) groups into the PCS molecules, the ceramic yield of PCSCN can increase largely to over 80 %. The ceramization mechanism of PCSCN is investigated by FTIR, TG, XPS, ESR, NMR, Raman and XRD analyses. It is found that some crosslinking structures in PCSCN are formed between SiH bonds and CN groups from about 200 ℃, which can be responsible for the high ceramic yield. The existence of a little more N, O and free C elements in the pyrolysis products may inhibit the growth of crystalline β-SiC. Moreover, the PCSCN precursor can also be melt-spun into continuous fibers by tailoring its molecular weight and softening point. The oxidized PCSCN fiber with relatively low oxygen content can be pyrolyzed without melting, and the final SiC fiber with an oxygen content as low as 8.5 % is obtained.